Training Teachers for the Gifted and Talented A Comparison of Models - Maker, C. June.; ERIC Clearinghouse on Handicapped and Gifted Children ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Program models are described and successful practices are surveyed in training teachers for gifted and talented students. In a section on assumptions and issues, the teacher's role is discussed in terms of classroom innovation and development of attitudes, skills, and abilities in students; and alternatives for teacher training programs are outlined. Two criteria necessary for teachers of the gifted are noted to be an ability to relate effectively to the group of youngsters being taught and an openness to change; and suggestions for assessing teacher competency are given. Presented is an analysis of various preservice training programs and a comparison of the major methodological differences in them, as well as a review of past and current practices. Variations of inservice training models are described, compared, and contrasted, and evaluation results are reported for each of the following: summer institutes, demonstration centers, and service centers. Appended is a list of university training programs offering either graduate or undergraduate degrees in education of the gifted. (SB)
Availability: Council for Exceptional Children, 1920 Association Drive, Reston, Virginia 22091 ($3.95 publication number 117).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Trends; Exceptional Child Education; Gifted; Higher Education; Inservice Teacher Education; Models; Preservice Teacher Education; Program Effectiveness; Teacher Education; Teacher Qualifications; Teacher Role; Reports, Research